2011
DOI: 10.5402/2011/929868
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Massage Therapy for Reducing Pain, Anxiety, and Depression in Oncological Palliative Care Patients: A Narrative Review of the Literature

Abstract: A considerable number of cancer patients use complementary medicine therapies in order to alleviate different symptoms such as pain, anxiety, and depression, occurring in connection with cancer. This paper explores the question to what extent massage therapies are able to reduce the amount of pain, anxiety, and depression. For this purpose, a systematic literature analysis was carried out in the electronic databases and specialist journals. There is already evidence that massage therapies can influence the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 22 publications
(132 reference statements)
3
30
0
4
Order By: Relevance
“…Foot massage has also been found to have an effect on the reduction of lower limb edema in pregnancy (Coban & Sirin, 2010), decreased anxiety and depression in palliative care (Puthusseril, 2006), decreased agitation in dementia patients (Moyle, Johnston, & O'Dwyer, 2011 ), as well as decreased pain, depression, anxiety, stress, and weakness in cancer patients (Cassileth & Vickers, 2004;Quattrin et al, 2006;Falkensteiner et al, 2011;Kim & Oh, 2011). This study finding in line with Hayes and Cox'x's study found that a significant reduction of Mean Arterial Pressure (MAP) of 25 patients at Intensive Care Unit (ICU) after foot massage (Smith et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foot massage has also been found to have an effect on the reduction of lower limb edema in pregnancy (Coban & Sirin, 2010), decreased anxiety and depression in palliative care (Puthusseril, 2006), decreased agitation in dementia patients (Moyle, Johnston, & O'Dwyer, 2011 ), as well as decreased pain, depression, anxiety, stress, and weakness in cancer patients (Cassileth & Vickers, 2004;Quattrin et al, 2006;Falkensteiner et al, 2011;Kim & Oh, 2011). This study finding in line with Hayes and Cox'x's study found that a significant reduction of Mean Arterial Pressure (MAP) of 25 patients at Intensive Care Unit (ICU) after foot massage (Smith et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Study literatures showed that foot massage in different points of massage and and times effected different blood pressure in the treatment group (Falkensteiner, Mantovan, Müller, & Them, 2011). However, there is no a study that assess the effectiveness of foot massage in pregnant women with preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a patient with comfort and ease and promotes the quality of life (16,(30)(31)(32). Increasing trust and safety among patients is easily accepted by them (25), a fact which leads to more acceptances of therapies and cooperation on patients' side (33).…”
Section: Discussionmentioning
confidence: 99%
“…The only meta-analysis was the study conducted by Lee et al (24), and the rest of them were reviews (25)(26)(27). Although the year of study, inclusion and exclusion criteria, and the number of reviewed papers were different, the results of all four studies indicated that massage therapy could be useful as an effective non-pharmacological method to control pains in patients with cancer.…”
Section: Review and Meta-analysis Studiesmentioning
confidence: 99%
“…While massage therapy has been extensively studied to relieve cancer or other chronic pain conditions ( Bardia, Barton, Prokop, Bauer, & Moynihan, 2006 ;Dhanani, Caruso, & Carinci, 2011 ;Ernst, 2009 ;Falkensteiner, Mantovan, Müller, & Them, 2011 ;Furlan, Imamura, Dryden, & Irvine, 2009 ;Lafferty, Downey, McCarty, Standish, & Patrick, 2006 ), fewer experimentally designed studies have evaluated the effect of massage therapy as an adjunct to analgesic administration in patients with acute surgical pain ( Drackley, Degnim, Jakub, Cutshall, Thomley, Brodt, & Boughey, 2012 ;Shorofi , 2011;Wentworth, Briese, Timimi, Sanvick, Bartel, Cutshall, & Bauer, 2009 ). The majority of these studies evaluated massage therapy in postoperative cardiac surgical patients ( Albert et al, 2009 ;Cutshall, Wentworth, Engen, Messner, & Wood, 2010;Braun et al, 2012 ;Hattan, King, & Griffi ths, 2002 ;Kshettry, Carole, Henly, Sendlebach, & Kummer, 2006 ).…”
Section: Introductionmentioning
confidence: 98%